Seasonal variations in surface ozone as influenced by Asian summer monsoon and biomass burning in agricultural fields of the northern Yangtze River Delta - Tang, Haoye; Liu, Gang; Zhu, Jianguo; Han, Yong; Kobayashi, Kazuhiko (Atmospheric research, 2013)
Surface ozone (O3) concentration was measured continuously at an agricultural site of Jiangdu in the northern Yangtze River Delta (YRD), China for the period from March 2007 to December 2011. Extremely high O3 concentrations ([O3]) were frequently observed in May and June with the highest hourly mean of 144ppb. The monthly 7-h mean of [O3] showed a bimodal pattern in the seasonal change with peaks in June and October. The depression of [O3] in summer was due mostly to the monsoonal climate, which was adverse to photochemical O3 generation. Analyses of the wind direction and air mass trajectories showed that pollutants from the industrialized area of YRD were carried by the prevailing wind, causing an increased [O3] in the spring, whereas, in the summer, frequent incursions of maritime air mass diluted the high [O3] in the polluted air mass. Furthermore, it was found that extensive open crop residue burning in central eastern China made a significant contribution to the peak [O3] in June. The increase of [O3] by the residue burning in June was estimated to be 39% on sunny days and 27% on rainy days. The inter-annual variation of [O3] showed that [O3] in June tends to be lower in the years with more maritime air mass incursions, and the lowest [O3] in June 2008 could be partially attributed to the low frequency of residue burning events. This study has thus demonstrated that the variations in marine air mass incursions as influenced by the monsoonal climate and the open crop residue burning are the major determinants of the seasonal trends in surface [O3] across the agricultural areas of the northern YRD. ► Long-term surface O3 was observed for the first time in the northern Yangtze River Delta. ► Pollutants from industrialized area with the prevailing wind increase O3 in spring. ► Monsoonal incursions of the maritime air masses depress O3 in summer. ► Crop residue burning makes a significant contribution to the peak O3 in June.